2016
DOI: 10.1007/s13760-016-0617-2
|View full text |Cite
|
Sign up to set email alerts
|

Early pain relief from orthostatic headache and hearing changes in spontaneous intracranial hypotension after epidural blood patch

Abstract: Spontaneous intracranial hypotension (SIH) is a neurological condition characterized by orthostatic headache (OH), low cerebrospinal fluid (CSF) pressure and diffuse pachymeningeal enhancement on brain magnetic resonance imaging (MRI). Hearing changes (HC) are also a common clinical finding. At present, epidural blood patch (EBP) is the most recommended treatment. Our study aimed at describing clinical variability of SIH patients. We also aimed at measuring the EBP efficacy on OH and HC in patients affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The headache location was most commonly diffuse, occipital, or frontal. 15, [26][27][28][29] Table 1 shows all the other signs and symptoms reported and their pooled estimates of proportions. Downloaded From: https://jamanetwork.com/ on 01/10/2021…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The headache location was most commonly diffuse, occipital, or frontal. 15, [26][27][28][29] Table 1 shows all the other signs and symptoms reported and their pooled estimates of proportions. Downloaded From: https://jamanetwork.com/ on 01/10/2021…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The current study presents data on various aspects of upright posture intolerance in patients with headaches due to intracranial hypotension before and after epidural blood injection using a semiquantitative assessment. Previous studies have reported the effectiveness of epidural blood injection on orthostatic headaches and hearing difficulties in patients with intracranial hypotension (Ferrante, Olgiati, Sangalli, & Rubino, ; So et al., ; Wu et al., ). Our study provides additional information regarding another important aspect of intracranial hypotension syndrome, which is upright posture intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patches have positive outcomes and an overall efficacy of approximately 90% [ 21 ]. However, several complications such as hearing changes [ 22 ], vision loss [ 23 ], and transient bladder and fecal incontinence [ 24 ] have been reported with the procedures. Some trials have suggested the greater efficacy of radiologic-targeted EBPs, compared to blind EBPs, for treating spontaneous intracranial hypotension [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%